Javanese-Islamic Mysticism In Serat Nitisruti By Prince Karanggayam - Bahroon Ansori; Thiyas Tono Taufiq (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
Javanese-Islamic mysticism believes that humans can find God (in union with Him) through wisdom. The concepts are similar to Sufism, such as Ittiḥād, ḥulūl, and Waḥdat al-wujūd. This study aims to discover the formulation of Javanese-Islamic mysticism teachings in Serat Nitisruti by Prince Karanggayam. The primary data were obtained from Javanese manuscripts, namely Serat Nitisruti, compiled by Prince Karanggayam (1591-1612 AD), from the early days of Pajang to the end of Pajang (controlled by Mataram). Prince Karanggayam was the first poet and an Islamic preacher in Pajang. This study applies the cultural analysis of Koentjaraningrat. The results show that Javanese-Islamic mysticism in Serat Nitisruti has four stages; purification of kapti (heart), atunggal marang Gusti (union with God), nugrahaning widhi (God’s blessing), and the last is application stage, i.e., managing the world or doing actual actions. If someone can reach the third stage, he deserves to be called waskitha. However, if those stages are not completed with the application stage, the result will be imperfect. Therefore, Javanese-Islamic mysticism has its reasoning and logic by Javanese society at that time, namely, ngelmu kanthi laku; knowledge must be accompanied by actual actions.Contribution: This study uncovers the teachings of the spiritual journey based on local wisdom among Javanese Muslims, as contained in Serat Nitisruti, which Prince Karanggayam compiled.